Roux-en-Y gastric bypass is superior to sleeve gastrectomy regarding postoperative diarrhea and nausea: a multicenter prospective study - Finze, Alida; Rajjo, Hiba; Rheinwalt, Karl Peter; Plamper, Andreas; Gärtner, Daniel; Popp, Anna; Reißfelder, Christoph; Otto, Mirko; Blank, Susanne (Bariatric surgical practice and patient care, 2025)
Background: Bariatric surgery (BS) currently is the most effective treatment for severe obesity. To our knowledge, no data comparing different bariatric procedures regarding differences in gastrointestinal symptoms have been published. - Methods: For this multicenter, prospective, nonrandomized clinical trial in Germany, 310 patients underwent screening, and 124 patients completed the study. Patients completed the following standardized questionnaires preoperatively and at 6 and 12 months after surgery: Gastrointestinal quality of life index, bowel disease questionnaire, and Cleveland clinic incontinence score. - Results: Mean patient age was 44.4 years. Mean body mass index prior to surgery was 45.1 kg/m2. Physical function improved significantly after surgery (31.9 vs. 62.1 and 62.3, respectively, p < 0.001). Nausea and diarrhea symptoms worsened 12 months after sleeve gastrectomy (SG; p = 0.025 and p = 0.017, respectively). Constipation improved 12 months after SG (p = 0.006). Multivariate analysis revealed SG as an independent predictive factor for diarrhea (p = 0.026). Physical and emotional function improved for Roux-en-Y gastric bypass and SG. - Conclusion: This study highlights differences in symptom outcomes after different bariatric procedures. Significant changes in bowel habits were seen especially after SG. Overall, BS improves quality of life. Side effects of surgery should not be a contraindication for surgery. However, patients can be educated regarding possible side effects, and the surgical procedure can be chosen individually.